The Construction of Textual Authority in German Literature of the Medieval and Early Modern Periods - Poag, James F.; Baldwin, Claire (UNC Studies in the Germanic Languages and Literatures, 2001)
Interest in the intersections of various kinds of discourse provides the basis for a closer look at diverse textual strategies of cultural legitimation. This collection presents an introductory essay and eleven studies (written in English and German) that address claims to authority associated with differing kinds of texts from such varied perspectives as political performance, popular culture, history of science, interrelations between verbal texts and other arts, and artistic professionalism. Read together, these studies illuminate historical contingencies and reveal important changes in the "technologies of authority" from the twelfth through the eighteenth centuries. The contributors are Claire Baldwin, Thomas Cramer, Arthur Groos, Walter Haug, C. Stephen Jaeger, Jane O. Newman, James F. Poag, David Price, Rüdiger Schnell, Lynne Tatlock, Horst Wenzel, and Gerhild Scholz Williams.